The Relationship between Financial Ratios and Stock Prices Case Study Listed Companies in Industrial Packaging - Datsiri, Phawinee; Chansom, Nakamol (Journal of Humanities and Social Sciences, Rajapruk University, 2021)
The objectives of this research were to study the relation between financial ratios and stock price case study listed companies in Industrial Packaging Business Sector in the Stock Exchange of Thailand. The study was period of 2017 to 2020 using seventeen companies. The financial ratios using 15 ratios divided into five sides Liquidity Ratios, Activity Ratios, Leverage Ratios, Profitability Ratios, and Market Value Ratios. The closing price of each year was used in investigation were used in this were Pearson correlation and multiple regression analysis. The result shows that four financial ratios had relationships with stock price in Industrial Sector Packaging. On the one hand, Inventory Turnover and Earnings per Share were significantly positive related to market stock price. On the other hand, Debt to Assets Ratio and Interest Coverage Ratio were significantly negative related to market stock price.